QSAR and Molecular Docking Studies of 5-benzylideno-2-adamantylthiazol[3,2-b][1,2,4]triazol-6(5H)ones Derivatives as Antimicrobial Activity - Chitre, Trupti S; Parse, Sheetal; Asgaonkar, Kalyani; Khedekar, Vijay; Jadhav, Shivani; Pradhan, Kunal (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim and Background: Bacterial Infection is a leading cause of death worldwide. Triazoles and thiazolinones (fused) have been reported to possess many biological activities including antibacterial activity. To study 2D and 3D QSAR followed by Molecular Docking studies to generate new chemical entities (NCE’s) containing as pharmacophore for antibacterial activity. Materials and Methods: In the presented studies we have reported the results of QSAR studies for the 21 derivatives of triazole-thiazolinone synthesized by Tratrat et al. 2D and 3D QSAR studies were done by using V-Life software. The NCE’s were designed by using Lead grow tool in V-Life Software and screened by Lipinski screen. The designed compounds having the Lipinski score 5 were subjected to molecular docking studies with Staphylococcus aureus (DNA gyrase) enzyme by using autodock software. Results: The r2 and q2 for the 2D QSAR and 3D QSAR was found to be 0.9000 and 0.8730 respectively. Large number of molecules were generated by using Lead grow tool in V Life. Conclusion: The substitution pattern was established by using QSAR tool for better Antibacterial activity.
Keywords: Triazole-thiazolinone; Antibacterial; QSAR; Combilib; Docking; Molecular modelling studies